2013
DOI: 10.1002/cbin.10113
|View full text |Cite
|
Sign up to set email alerts
|

SiRNA‐targeted carboxypeptidase D inhibits hepatocellular carcinoma growth

Abstract: Carboxypeptidase D (CPD), a membrane-bound metallocarboxypeptidase that functions as a docking receptor for duck hepatitis B virus, is frequently overexpressed in human cancers. We have explored its expression pattern, clinical significance, and biological function of CPD in hepatocellular carcinoma (HCC). CPD expression was markedly elevated in HCCs relative to adjacent non-tumor liver tissues, as determined by quantitative real-time polymerase chain reaction and Western blot analysis. Immunohistochemistry sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…The correlation between some of the proteins selected for the verification analysis and HCC has been separately and independently reported previously (Table ). , Thus, the comprehensive expression profiles presented in this analysis provide supporting evidence for the involvement of the verified proteins in HCC development. To our knowledge, this is the first report showing the overexpression of DDX39, FBLN5, MARCKS, and SERPINH1 in association with HCC.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The correlation between some of the proteins selected for the verification analysis and HCC has been separately and independently reported previously (Table ). , Thus, the comprehensive expression profiles presented in this analysis provide supporting evidence for the involvement of the verified proteins in HCC development. To our knowledge, this is the first report showing the overexpression of DDX39, FBLN5, MARCKS, and SERPINH1 in association with HCC.…”
Section: Discussionsupporting
confidence: 62%
“… a The analysis was done on 31 HCC and 31 adjacent nontumorous samples. Bold formatted proteins are with ≤0.05 FDR p -value. b Proteins which were reported in previous studies in association with HCC. , c Paired t test. d FDR adjusted p -value according to Benjamini and Hochberg. …”
Section: Resultsmentioning
confidence: 99%
“…Data from the TCGA Fusion Gene Database showed that the some of the candidate genes form chimeras with a variety of partners in different tumor types, suggesting that they might locate in genomic regions prone to chromosomal rearrangements [46,47] and/or have a role in carcinogenesis. The most frequently altered genes were CPD and CNOT2, whose overexpression was associated with survival, inhibition of apoptosis and angiogenesis in different cancer types [22,[48][49][50][51]. Regarding the other genes that were rarely rearranged across cancer, they might participate to the leukemic phenotype, even though not being the driver of transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, CPD immunostaining is higher in PCa than in benign prostate tissues . CPD levels are also elevated in hepatocellular carcinoma, as compared to benign liver tissue, whereas knockdown of endogenous CPD expression in Huh7 liver carcinoma cells reduces cell proliferation and increases apoptosis .…”
Section: Introductionmentioning
confidence: 95%